Magnetic fields in elliptical galaxies: using the Laing–Garrington effect in radio galaxies and polarized emission from background radio sources. Issue 1 (5th October 2021) - Shah, Hilay; Seta, Amit
ABSTRACT: Magnetic fields in elliptical galaxies are poorly constrained because of a lack of significant synchrotron emission from them. In this paper, we explore the properties of magnetic fields in ellipticals using two methods. First, we exploit the Laing–Garrington effect (asymmetry in the observed polarization fraction between radio galaxy jets) for 57 galaxies with redshifts up to 0.5. We use the differences in polarization fraction and rotation measure between the jet and counterjet to estimate the small- and large-scale magnetic fields in and around ellipticals (including their circumgalactic medium). We find that the small-scale field (at scales smaller than the driving scale of turbulence, approximately 300 pc) lies in the range 0.1–2.75 μG . The large-scale field (at scales of 100 kpc) is an order of magnitude smaller than the small-scale field. In the second method, we cross-match the Faraday rotation measures (RMs) of a few hundred (out of 3098) extragalactic radio sources with galaxy catalogues to explore the effect of the number and morphology of intervening galaxies on the observed RM distribution. We use both Gaussian and non-Gaussian functions to describe the RM distribution and to derive its statistical properties. Finally, using the difference in the observed polarization fraction between the intervening spirals and ellipticals, we estimate the small-scale magnetic fields at the centre of ellipticals to be ∼6 μG . Both methods with different observations and analysis techniques give magnetic field strengths consistent with previous studies (≤10 μG ). The results can be used to constrain dynamo theories and galaxy evolution simulations.